2016
DOI: 10.5505/tjtes.2016.59844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetylcysteine on neutrophil functions during experimental acute pancreatitis

Abstract: BACKGROUND: Systemic inflammatory responses and extrapancreatic vital organ impairment are mediated by activated neutrophil functions and products, such as oxygen-derived free radicals, in patients with acute pancreatitis (AP). The present study is an examination of effects of an antioxidant, N-acetylcysteine (NAC), on local and systemic histopathological changes and neutrophil functions during AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…After duplicate articles were removed and articles screened for eligibility, full text of 24 articles were reviewed. Twelve of these articles were excluded for administration of multiple agents, texts not available in English and the administration of agents post induction of pancreatitis 23–34 . Twelve RCTs were included in the systematic review and meta‐analysis 35–46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicate articles were removed and articles screened for eligibility, full text of 24 articles were reviewed. Twelve of these articles were excluded for administration of multiple agents, texts not available in English and the administration of agents post induction of pancreatitis 23–34 . Twelve RCTs were included in the systematic review and meta‐analysis 35–46 …”
Section: Resultsmentioning
confidence: 99%
“…Twelve of these articles were excluded for administration of multiple agents, texts not available in English and the administration of agents post induction of pancreatitis. [23][24][25][26][27][28][29][30][31][32][33][34] Twelve RCTs were included in the systematic review and meta-analysis. [35][36][37][38][39][40][41][42][43][44][45][46] The characteristics of the included studies are shown in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…A previous study suggested that N-acetylcysteine treatment ameliorated pulmonary and renal tissue damages in all microscopic parameters [ 15 ]. Other studies have shown that anti-HMGB1 treatment protected against renal injury in experimental acute pancreatitis [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While various antioxidant enzymes depletion, including superoxide dismutase (SOD), catalase, and GSH, often occurred in pancreatitis, it is acknowledged that the replenishment of antioxidant agents, e.g. NAC, have been recognized as a feasible idea for acute pancreatitis therapy (Atayoglu, 2016 ). However, a recent double-blind placebo (PL)-controlled randomized pilot study indicated the simple supplementation with antioxidant to patients obtained no additional therapeutic benefits on endocrine and exocrine function, fibrosis progression, and the severity of oxidative stress and inflammation (Singh et al., 2019 ).…”
Section: Formulation Approaches For Acute Pancreatitismentioning
confidence: 99%